EFEK PENGGANDA PENGELUARAN WISATAWAN NUSANTARA Studi Kasus : Destinasi Ketep Pass Kabupaten Magelang - , mulyadi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted in Ketep Pass, since it is a primary tourism destination, after Borobudur Temple, in Magelang regency. The multiplier effects, in this context, measure the success of tourism development in a tourism destination. For that reasons, the research attempts to identify the extent to which the success of Ketep Pass development as a primary tourism destination affects the local economy. The research aims to identify the tourist motivation to spent money on activities in Ketep Pass. Next, to identify the magnitude of multiplier effect of tourists expenditure in Ketep Pass. Last, to devise a guideline for Ketep Pass development in an attempt to increase the number of tourists expenditure. It uses both quantitative and qualitative methods that employ keynesian multiplier models analysis and descriptive analysis, respectively. The research found that what motivate the tourist to visit Ketep Pass are for relaxation and fun, while tourists motivation to engage in activities or attraction in this destination consists of several factors such as seasonal tickets, curiousity, following friends or group, and remembrance. The multiplier effect of tourists expenditure in Ketep Pass amount to 1,14. The figure indicates that the tourist expenditure in Ketep have impacts on local economy.